Evaluation of Scientific Workshops: Proposal from Education and Scientific Communication - Jiménez Taboada, Nallely; Ojeda Santiago, Victoria Adriana (Emerging Trends in Education, 2021)
In Public Science Communication (PSC), since more than ten years ago, exists the need to assess scientific communicators, based on three axes: evaluation by the public, evaluation by partners and self-evaluation. Although different authors make suggestions about what attitudes, skills and knowledge should a science communicator have, there is not a common instrument that indicates what and how to evaluate them. In consequence, the aim of this article is to propose an instrument that considers several aspects that could be evaluated in a science workshop facilitator through documental review and qualitative analysis of different papers. We defined 8 dimensions and 19 categories divided in three types of possible evaluations. The instrument is based on an educational and communicative approach on which formal and informal education environments have a common ground, i.e., the interest to develop a scientific culture in which school-based and informal education collaborate by joining theoretical and empirical efforts from their different research projects. It is expected to be a guide for scientifical groups and different types of scientific communicators, so they are able to adapt it to their needs and circumstances.